Diasporic Feminist Theology : Asia and Theopolitical Imagination - Kang, Namsoon (Book collections on Project MUSE., 2015)
How do we navigate the question of identity in the fluid and pluralist conditions of postmodern society? Even more, how do we articulate identity as a defining particularity in the disappearance of borders, boundaries, and spaces in an increasingly globalist world? What constitutes identity and the formation of narratives under such conditions? How do these issues affect not only discursive practices, but theological and ethical construction and practice? This volumes explores these issues in depth. Diasporic Feminist Theology attempts to construct feminist theology by adopting diaspora as a theopolitical and ethical metaphor. Namsoon Kang here revisits and reexamines today's significant issues such as identity politics, dislocation, postmodernism, postcolonialism, neo-empire, Asian values, and constructs diasporic, transethnic, and glocal feminist theological discourses that create spaces of transformation, reconciliation, hospitality, worldliness, solidarity, and border-traversing. This work draws on diverse sources from contemporary critical discourses of diaspora studies, cultural studies, ethnic studies, postmodernism, postcolonialism, and feminism and feminist theology from a transterritorial space. This book is a landmark work, providing a comprehensive discourse for feminist theology today.